2015
DOI: 10.4238/2015.october.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Thermotherapy-induced reduction in glioma invasiveness is mediated by tumor necrosis factor-alpha

Abstract: ABSTRACT. Thermotherapy has been proven to be effective for the treatment of various tumors, including glioma. We determined whether tumor necrosis factor-alpha (TNF-α) is involved in the regulation of the biological processes of glioma development. Reverse transcriptionpolymerase chain reaction (RT-PCR) and immunocytochemistry were used to investigate the levels of TNF-α mRNA and heat shock factor-1 (HSF1) protein, respectively, in glioma cells. Radioimmunoassay was used to dynamically monitor the contents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This immunogenic reaction upon tissue damage may lead to enhanced anti-tumor responses after adoptive transfer of tumor antigen-specific T cells even in immunologically cold tumors, such as EwS [30,33]. Interestingly, EwS itself secretes TNF upon irradiation and local hyperthermia [34,35]. Various research groups have observed an upregulation of TNF mRNA and protein levels in response to irradiation in a time-dependent manner in TNF producing EwS cell lines [29,34,36].…”
Section: Discussionmentioning
confidence: 99%
“…This immunogenic reaction upon tissue damage may lead to enhanced anti-tumor responses after adoptive transfer of tumor antigen-specific T cells even in immunologically cold tumors, such as EwS [30,33]. Interestingly, EwS itself secretes TNF upon irradiation and local hyperthermia [34,35]. Various research groups have observed an upregulation of TNF mRNA and protein levels in response to irradiation in a time-dependent manner in TNF producing EwS cell lines [29,34,36].…”
Section: Discussionmentioning
confidence: 99%